AIEST: Review of an Institution Dedicated to Tourism Knowledge - Pechlaner, Harald (Anais Brasileiros de Estudos Turísticos, 2016)
The AIEST (Association Internationale D’Experts Scientifique de Tourisme) has been in existence as the International Association of Scientific Experts in Tourism for 65 years! It is therefore the world's oldest association for tourism research. This age not only stands for tradition, but also for a commitment to the efforts directed towards establishing tourism as a science.